Design of Ta gradient layer to improve adhesion strength between Cu substrate and DLC film. (September 2022) - Wu, Yanxia; Shi, Bang; Liu, Ying; Wang, Limin; Gao, Jie; Shen, Yanyan; Wang, Yongsheng; Ma, Yong; Yu, Shengwang
Abstract: Tantalum (Ta) gradient transitional layer, which was prepared by double-glow plasma surface alloying technology, was designed to improve the adhesion strength between Cu substrate and diamond-like carbon (DLC) film. The microstructure, morphology, mechanical and tribological properties of samples were characterized and analyzed. The results showed that the adhesion strength and tribological properties were improved greatly by Ta interlayer. The surface roughness of the sample was mainly depended on the Ta deposition layer, increased with prolonged alloying time. The adhesion strength between Cu substrate and DLC film increased obviously with Ta interlayer. Notably, the sample with Ta alloying time of 30 min showed highest critical load arise from that Ta gradient interlayer can form intertwined planes near Cu substrate and Ta2 C near DLC film. Furthermore, it showed lower friction coefficient (∼0.22) and the lowest wear rate (3 × 10 −5 mm 3 /Nm), which was attributed to the highest content of sp 3 C, lower surface roughness and more content of Ta2 C grains in the sample. Highlights: Ta exist in different form at the interlayer: α-Ta in the bulk, amorphous Ta near the Cu substrate, while TaC near the Diamond-like carbon layer. The adhesion strength and tribological properties of bare Cu substrate was improved greatly by Ta interlayer. Ta2 C grains in the sample were beneficial to maintain high adhesion strength and excellent tribological properties.